Perlindungan Hukum Pemegang Saham Minoritas Terhadap Implikasi Praktik Insider Trading dalam Perdagangan Saham di Pasar Modal - Elza Syarief; Junaidi Junaidi (Journal of Law and Policy Transformation, 2021)
The capital market is a means provided in order to find sources of financing and as a means of investment that involves all potential public funds, both those available domestically and those available abroad. This study uses a normative science study using a librarian study in the form of law and is assisted by primary data sources and secondary data sources. The results show that minority shareholders own less than 5% of the total shares traded in the capital market. Meanwhile, insider trading is a practice in which a corporate insider transacts securities using exclusive information that they have that is not yet available to the public. The position of Minority Shareholders regarding the practice of insider trading in trading shares in the capital market is the cause of the practice of insider trading. Therefore, legal protection for minority shareholders in the practice of insider trading in stock trading in the capital market is carried out by applying applicable laws and using the theory of legal protection by Philipus M. Hadjon.